Meningkatkan Prestasi Bahasa Inggris melalui Intervensi Pembelajaran Berbasis Duolingo: Peran Prediktif dari Intensitas Penggunaan: Meningkatkan Prestasi Belajar Bahasa Inggris Melalui Intervensi Pembelajaran Berbasis Duolingo: Peran Intensitas Penggunaan dalam Peningkatan Kemampuan Belajar - Yulia Wahyuningsih; Mujiono; Lasim Muzammil (Language Development Center, 2026)
Background: The rapid growth of MALL technology has positined Duolingo establish itself as one of the top language learning platforms in the modern era. However, uncertainty persists regarding how variable user frequency affects outcomes, notably when learners have diverse initial skill levels․ Purpose: The study examined whether an individual's initial level of performance influenced a structured Duolingo activity that improved their English skills․ The study further explored the correlation between the application of intensive treatment and outcomes after testing․ Method: This study used a one-group pretest–posttest quasi-experimental design․ It involved 60 EFL learners completing a structured Duolingo intervention․ Standardized tests were used to measure proficiency before and after the program․ Usage logs record session timing and duration․ ANCOVA was used to test the effectiveness of the intervention and the predictive role of usage intensity․ Results and Discussion: Descriptively, the low-intensity group achieved the highest unadjusted posttest mean (M = 80.40). However, interpretation relied on ANCOVA-adjusted posttest scores controlling for pretest performance. The results showed a significant effect of usage intensity, F(2,57) = 4.421, p = .016, η² = .128. Learners with moderate-to-low engagement demonstrated greater learning gains than high-intensity users, indicating that regulated use supports more effective English learning. Conclusions and Implications: Results showed that learning English through Duolingo was effective when users were actively engaged and provided with appropriate guidance․This brings the study's full circle to the point that what matters most is the fairness of involvement․ Therefore, it is recommended that protocols be established to prevent excessive use of this platform․ These strategies must be sufficiently data-informed to preserve effectiveness, sustainability, and pedagogical soundness of technologically equipped language instruction․